Autosomal dominant hypercalciuric hypocalcaemia: the calcium‐sensing receptor in renal calcium homeostasis and the impact of renal transplantation - Florance, James A.; Schollum, John B. W.; Pomeranc, Abigail; Endre, Zoltan H.; Walker, Robert J. (Internal medicine journal, 2024)
Calcium‐sensing receptors (CaSRs) are G protein‐coupled receptors that help maintain Ca2+ concentrations, modulating calciotropic hormone release (parathyroid hormone (PTH), calcitonin and 1,25‐dihydroxyvitamin D) by direct actions in the kidneys, gastrointestinal tract and bone. Variability in population calcium levels has been attributed to single nucleotide polymorphisms in CaSR genes, and several conditions affecting calcium and phosphate homeostasis have been attributed to gain‐ or loss‐of‐function mutations. An example is autosomal dominant hypercalciuric hypocalcaemia, because of a missense mutation at codon 128 of chromosome 3, as reported in our specific case and her family. As a consequence of treating symptomatic hypocalcaemia as a child, this female subject slowly developed progressive end‐stage kidney failure because of nephrocalcinosis and nephrolithiasis. After kidney transplantation, she remains asymptomatic, with decreased vitamin D and elemental calcium requirements, stable fluid and electrolyte homeostasis during intercurrent illnesses and has normalised urinary calcium and phosphate excretion, reducing the likelihood of hypercalciuria‐induced graft impairment. We review the actions of the CaSR, its role in regulating renal Ca2+ homeostasis along with the impact of a proven gain‐of‐function mutation in the CaSR gene resulting in autosomal dominant hypercalciuric hypocalcaemia before and after kidney transplantation.